Desenvolvimento de competências em medicina de família e comunidade: fortalezas e dificuldades em um programa de residência médica na perspectiva do residente egresso - Crisanto, Laís Izabel Maia Melo (2020)
Introduction: Training in family medicine (FM) involves a complex set of skills. SBMFC developed a competency-based curriculum in the face of the expansion of MFC residency programs in Brazil, to guide the training of young family physicians. This article aimed to analyze the facilitating and limiting factors in the development of skills during residency in FM. Methods: This is a case study with a qualitative analysis, with a structured eletronic questionnaire applied to FM graduated from the Family Medicine Residency Program at Hospital Universitário Onofre Lopes (FMRP/HUOL) since 2016, with questions about socio-demographic data and referring to the residency program, with subsequent descriptive analysis of the data obtained. Individual interviews were conducted to deepen the understanding of the skills to be developed in the program and how this process took place at the residence. A categorical analysis based on Bardin about the content of the interviews was carried out. Results: A total of 7 graduates were interviewed, and 9 responded to the virtual questionnaire, corresponding to a significant part of the 11 residents who concluded the program in the years 2016 to 2019. The units of analysis of the interviews were grouped into 3 a priori categories (Competencies of MFC to be addressed during the residency; Factors that influenced the development of MFC skills; Development of skills in communication skills and clinical reasoning in FMRP/HUOL) and 1 category a posteriori (Proposed analysis on training for FM). Discussion: The SBMFC`s competency-based curriculum was perceived by the FM graduates as a well-known and applied instrument in the FMRP/HUOL, so much so that the skills cited in the interviews are in line with the categories found in the aforementioned curriculum. The contact with the preceptorship and the importance of the preceptor in the development of these competences consisted of very recurrent speeches in all interviews, being denoted as an important facilitator for the development of the resident during the program; the resident's autonomy was also frequently cited in the sense of being a fundamental requirement for the development of skills and better use of the residency program, which corroborates with the learning of adults and brings challenges to the preceptorship and to the planning of theoretical spaces-practical and evaluative, in addition to practice scenarios. Conclusions: FMRP/HUOL graduates are, in general, young doctors graduated from institutions whose curriculum has met the reform proposed by the DCN, and are motivated by the diversity of skills in the specialty. Preceptorship was perceived as a fundamental factor for the development of skills. The reform of the FMRP/HUOL curriculum, associated with better teaching-service dialogue and structuring of the Health Care Network in Natal, and finally the enhancement of the figure of the preceptor, can bring numerous benefits and new challenges to the municipality's health system.